Secured agriculture sensor data based on end-to-end encryption using raspberry pi - Choo, Jia Huey (2025)
The rise of smart agriculture in Malaysia, powered by IoT sensor networks, has transformed farming by enabling real-time monitoring of soil moisture, temperature, and environmental conditions. However, much of this sensor data is transmitted without encryption, exposing it to risks such as interception, tampering, and unauthorised access. This project addresses these security concerns by developing a secure data collection and visualisation system using Raspberry Pi and Node-RED. The system integrates multiple robust encryption algorithms—AES-128, AES-256, ChaCha20, and Twofish—for end-to-end data protection. Additionally, a benchmarking tool was developed to evaluate and compare the performance of these algorithms in terms of speed, memory, CPU usage, and encryption overhead. The final outcome is a lightweight, replicable solution for secure smart agriculture systems that enhances trust, integrity, and data privacy in IoT-based farming environments.